Interaction between acinetobacter haemolyticus and CR (VI): the XAFS perspective - Quek, Hsiao Pei (Nova Science Publishers, Inc., 2011)
This important book discusses the ethical code regarding possible introduction of exogenous bacterial species into the environment, as well as various other applications of bacteria in environmental biotechnology.